A mitochondria-targeting magnetothermogenic nanozyme for magnet-induced synergistic cancer therapy. (August 2020) - Shen, Jinchao; Rees, Thomas W.; Zhou, Zhiguo; Yang, Shiping; Ji, Liangnian; Chao, Hui
Abstract: Magnetic hyperthermia therapy (MHT) and chemodynamic therapy (CDT) are non-invasive in situ treatments without depth limitations and with minimum adverse effects on surrounding healthy tissue. We herein report a mitochondria-targeting magnetothermogenic nanozyme (Ir@MnFe 2 O 4 NPs) for highly efficient cancer therapy. An iridium(III) complex (Ir ) acts as a mitochondria-targeting agent on the surface of MnFe 2 O 4 NPs. On exposure to an alternating magnetic field (AMF), the Ir@MnFe 2 O 4 NPs induce a localized increase in temperature causing mitochondrial damage (MHT effect). Meanwhile glutathione (GSH) reduces Fe(III) to Fe(II) on the NPs surface, which in turn catalyzes the conversion of H2 O2 to cytotoxic OH (CDT effect). The depletion of GSH (a OH scavenger) increases CDT efficacy, while the localized increase in temperature increases the rate of conversion of both Fe(III) to Fe(II) and H2 O2 to OH further enhancing the CDT effect. In addition, the disruption of cellular redox homeostasis due to CDT, leads to greater sensitivity of the cell towards MHT. This nanoplatform integrates these excellent therapeutic properties, with two-photon microscopy (TPM) (demonstrated in vitro ) and magnetic resonance imaging (MRI) (demonstrated in vivo ) to enable the precise and effective treatment of cancer. Graphical abstract: Mitochondria-targeting nanoparticles (Ir@MnFe2 O4 NPs) have been synthesized for cancer treatment. The nanoparticles combine magnetic-hyperthermal therapy (MHT) with chemodynamic therapy (CDT), generating localized temperature increase and cytotoxic OH under an alternating magnetic field. The NPs can also be used for two-photon microscopy and MRI. This nanoplatform blends MHT, CDT and imaging for the potent and precise therapy of cancer. Image 1